Abusive Supervision dan Quiet Quitting Pada Buruh Perempuan di Industri Manufaktur - Astrawan, Muhammad Indra; Alamsyah, Rifan (Flourishing Journal, 2025)
This study aims to determine the relationship between abusive supervision dimension (credit stealing, belittling behavior, yelling, and scapegoating) and quiet quitting dimension (lack of motivation, detachment, and lack of initiative) among female workers in the manufacturing industry. This study uses a correlational quantitative approach with a purposive sampling technique. There were 486 female workers at a cigarette company as respondents. This study used two measuring instruments, namely the abusive supervision scale and the quiet quitting scale. Data analysis in this study used the Spearman rank correlation. The results showed that all dimensions of abusive supervision had no significant relationship (p > .05) with the dimension of lack of motivation. Meanwhile, in the dimension of detachment, all dimensions of abusive supervision showed a significant positive relationship (p < .001). Furthermore, the dimension of lack of initiative had three dimensions of abusive supervision, namely belittling behavior (r = 0.336, p < .001), yelling (r = 0.310, p < .001), and scapegoating (r = 0.293, p < .001), which also had a significant positive relationship. The findings of this study emphasize the need for leadership training with healthy communication and safe feedback system to minimize abusive supervision and quiet quitting in the workplace. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara dimensi abusive supervision (credit stealing, belittling behaviour, yelling, dan scapegoating) terhadap dimensi quiet quitting (lack of motivation, detachment, dan lack of initiative) pada buruh perempuan di industri manufaktur. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan teknik pengambilan sampel menggunakan purposive sampling. Terdapat 486 pekerja buruh perempuan perusahaan rokok sebagai responden. Penelitian ini menggunakan dua alat ukur, yaitu Abusive Supervision Scale dan Quiet Quitting Scale. Adapun analisis data dalam penelitian ini menggunakan uji korelasi Spearman rank test. Hasil penelitian menunjukkan bahwa seluruh dimensi dari abusive supervision tidak memiliki hubungan yang signifikan (p > .05) dengan dimensi lack of motivation. Sementara itu, pada dimensi detachment menunjukkan bahwa seluruh dimensi abusive supervision menunjukkan hubungan positif yang signifikan (p < .001). Pada dimensi lack of initiative terdapat tiga dimensi abusive supervision, yaitu belittling behaviour (r = 0.336, p < .001), yelling (r = 0.310, p < .001), dan scapegoating (r = 0.293, p < .001) yang juga memiliki hubungan positif yang signifikan. Temuan dari penelitian menekankan perlunya pelatihan kepemimpinan dengan komunikasi yang sehat dengan sistem umpan balik yang aman untuk meminimalkan perilaku abusive supervision dan quiet quitting di lingkungan kerja.